Trends and Challenges in Forensic Image Processing: A Bibliometric Study - WIraagni, Idha Arfianti; Saputra Yadnya , Komang; Widiningsih , Dewi; Bhima Nareshwara , Adhitya; Eka Ganda Winata , I Putu; Setya Nugroho , Florantia; Dwi Angesti Putri , Refly; Hidayat , Syukriadi; Sukma Wahyuni , Elvira; Firdaus; Erwandi Mohamad Haron, Didi (Universitas Ahmad Dahlan, 2025)
Forensic image processing plays a pivotal role in modern criminal investigations by enhancing, analyzing, and interpreting visual evidence. This bibliometric study aims to evaluate the research trends, influential publications, and collaborative networks in forensic image processing over the past two decades. This study analyzes global research trends in forensic entomology using data from the Scopus database spanning 1962 to 2024, with data visualized through VOSviewer. A total of 4,463 articles were identified, with an average productivity of 72 papers per year. Results reveal a significant increase in research outputs, with dominant contributions from countries excelling in advanced computational technologies. Current hot topics in the field include digital forensic, deep learning, convolutional neural network, and diagnostic imaging. This study provides valuable insights into the evolution of forensic image processing research and identifies future directions for technological advancements and interdisciplinary collaborations.